Strategies for Poly(3-hydroxybutyrate) Production Using a Cold-Shock Promoter in Escherichia coli - Boontip, Thanawat; Waditee-Sirisattha, Rungaroon; Honda, Kohsuke; Napathorn, Suchada Chanprateep (Frontiers in Bioengineering and Biotechnology, 2021)
The present study attempted to increase poly(3-hydroxybutyrate) (PHB) production by improving expression of PHB biosynthesis operon derived from Cupriavidus necator strain A-04 using various types of promoters. The intact PHB biosynthesis operon of C. necator A-04, an alkaline tolerant strain isolated in Thailand with a high degree of 16S rRNA sequence similarity with C. necator H16, was subcloned into pGEX-6P-1, pColdI, pColdTF, pBAD/Thio-TOPO and pUC19 (native promoter) and transformed into E. coli JM109. While the phaCA-04 gene was insoluble in most expression systems tested, it became soluble when it was expressed as a fusion protein with trigger factor (TF), a ribosome associated bacterial chaperone, under the control of a cold shock promoter. Careful optimization indicates that the cold-shock cspA promoter enhanced phaCA-04 protein expression and the chaperone function of TF play critical roles in increasing soluble phaCA-04 protein. Induction strategies and parameters in flask experiments were optimized to obtain high expression of soluble PhaCA-04 protein with high YP/S and PHB productivity. Soluble phaCA-04 was purified through immobilized metal affinity chromatography (IMAC). The results demonstrated that the soluble phaCA-04 from pColdTF-phaCABA-04 was expressed at a level of as high as 47.42.4 % of total protein and pColdTF-phaCABA-04 enhanced soluble protein formation to approximately 3.09  4.1 times higher than that from pColdI-phaCABA-04 by both conventional method and short induction method developed in this study. Cultivation in a 5-L fermenter led to PHB production of 89.82.3% PHB content, a YP/S value of 0.38 g PHB/g glucose and a productivity of 0.43 g PHB/(Lh) using pColdTF-phaCABA-04. The PHB film exhibited high optical transparency and possessed Mw 5.79×105 Da, Mn 1.86×105 Da and PDI 3.11 with normal melting temperature and mechanical properties.